2021
DOI: 10.1029/2020ef001832
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Responses of Summer Precipitation in China to 1.5°C Global Warming in Transient and Stabilized Scenarios

Abstract: The Paris Agreement adopted at the UNFCCC 21st conference of parties in 2015 aims to limit global warming to less than 2°C and to pursue efforts to limit the global warming level to 1.5°C (UNFCCC, 2015). The Agreement nevertheless did not mention any pathways to reach the goal. There are actually different scenarios to achieve the 1.5/2°C warming target. At least two possibilities are offered to us, with either a transient warming scenario or a stabilized one (Zhai et al., 2017). Although the two pathways can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…As shown in Figure S1 in Supporting Information S1, for CESM‐LEN, the response pattern of LDDH characteristics is generally consistent with that from CMIP multimodels (Figures 3 and 5), although CESM‐LEN shows a less intense increase in LDDH frequency and magnitude over southern China (such as Tibetan Plateau and South China) compared to CMIP models. This aligns with previous studies (He et al., 2019; Jiang et al., 2021) showing that the response of extreme events to global warming in CESM‐LEN is similar to that of the CMIP5 multimodel mean.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Figure S1 in Supporting Information S1, for CESM‐LEN, the response pattern of LDDH characteristics is generally consistent with that from CMIP multimodels (Figures 3 and 5), although CESM‐LEN shows a less intense increase in LDDH frequency and magnitude over southern China (such as Tibetan Plateau and South China) compared to CMIP models. This aligns with previous studies (He et al., 2019; Jiang et al., 2021) showing that the response of extreme events to global warming in CESM‐LEN is similar to that of the CMIP5 multimodel mean.…”
Section: Resultssupporting
confidence: 92%
“…The adverse is found in southeastern China, where the increase in LDDH count and magnitude is stronger in the stabilized scenario than the transient one. Similar behaviors have been found for summer precipitation and wet extremes, which show a more pronounced increase over southeastern China under the stabilized scenario compared with the transient one (Jiang et al., 2021).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Many studies used GCM simulations derived from the Coupled Model Inter-comparison Project (CMIP) under Representative Concentration Pathways or Shared Socioeconomic Pathways to examine the climate change in the transient 1.5 and 2 °C warmer GMST 9 11 . As the increase in GMST to 1.5 and 2 °C presents transiently in these simulations, CMIP GCMs cannot deal with the climate change under stabilized 1.5 and 2 °C global warming 9 , 12 14 , limiting the knowledge of the stabilized 1.5 and 2 °C warmer worlds. To fill the gap, a set of ensemble simulations using the Community Earth System Model (CESM) were produced under three low-warming scenarios in line with the Paris targets, including the stabilization pathways at 1.5 and 2 °C global warming 12 , which are widely used in many studies 15 17 .…”
Section: Background and Summarymentioning
confidence: 99%
“…As for the location, Seo et al (2013) showed that the multi-model ensemble-mean (MME) based on the Representative Concentration Pathway (RCP) 6.0 experiments of CMIP5 exhibited little meridional shift of EASM precipitation from the late twentieth century to the late twenty-first century. Possible future changes of the EASM are also investigated by many other studies (e.g., Li et al 2011;Freychet et al 2015;Chen and Bordoni 2016;Chen et al 2020;Zhou et al 2020;Jiang et al 2021;Endo et al 2021). A review is presented by Kitoh (2017).…”
Section: Introductionmentioning
confidence: 99%